Polarographic Study of Mixed Ligand Complexes in Aqueous Medium: Lead(II)-Thiourea-Glutamate System - Dongre, V.G. (Asian Journal of Chemistry, 2010)
The mixed ligand complexes of thiourea (tu) and glutamate (glu) ions withPb(II) have been studied polarographically in aqueous medium at 25 ± 0.5oCand μ = 1.0 M (NaClO4), Four mixed ligand complexes, viz.,[Pb(tu)(glu)]+, [Pb(tu)2(glu)]+, [Pb(tu)(glu)2] and [Pb(tu)2(glu)2] with theirrespective stability constants log β11 = 4.79, log β21 = 5.78, log β12 = 8.76 andlog β22 = 9.01 respectively were detected. The values of mixed ligand complexesare compared with the stability constants of the simple mono- andbis-complexes of the binary systems. The statistical factors in the complexationconstants were evaluated by following the procedure suggested by Walters. Thesimultaneous π-bonding between the metal ion and ligand was inferred from thedeviation observed in the relationship of log KN and (N - 1) where N representsthe coordination number as suggested by Van Panthaleion Van Eck.